Viscosity and friction reduction of double end capped polyalkylene glycol nanolubricants for eco friendly refrigerant - Mohd Zaki, Sharif; Wan Hamzah, Azmi; Mohd Fairusham, Ghazali; Nurul Nadia, Mohd Zawawi; Hafiz, Muhammad Ali (MDPI, 2023)
In sustainable tribology, researchers are investigating methods to enhance tribological performance by incorporating nanoparticles into lubricants. However, one potential drawback of this strategy is increased lubricant viscosity. The current study aimed to assess the impact of these nanoparticles on the viscosity and coefficient of friction (COF) of the nanolubricants. Three different nanolubricants were synthesized through a two-step process, including mono-nanolubricants (Al2O3/DEC PAG and SiO2/DEC PAG) and hybrid nanolubricants (Al2O3-SiO2/DEC PAG), at volume concentrations between 0.01% and 0.05%. The viscosity and shear flow behavior of these nanolubricants were evaluated using a digital rheometer, while the COF was measured using a Koehler four-ball tribometer. All the nanolubricants showed Newtonian behavior during the experiments. The dynamic viscosity velocity increment of SiO2/DEC PAG was found to be the lowest (1.88%), followed by Al2O3-SiO2/DEC PAG (2.74%) and Al2O3/DEC PAG (3.56%). The viscosity indices of all the nanolubricants were improved only at higher concentrations. At a volume concentration of 0.03%, the Al2O3-SiO2/DEC PAG nanolubricant reduced the COF by up to 8.1%. The results showed that the combination of nanoparticles, temperature, and volume concentration significantly influenced the viscosity and COF of nanolubricants. This study provides essential information for developing high-performance nanolubricants with improved viscosity and COF and advancing environmentally friendly tribology solutions.